Analysis of Natural and Artificial Lighting Assessment for SNI Compliance in Physics Laboratories - Danang Purwanto; Fadhil Muhammad; Akhmad Mujiburrokhman (Fakultas Teknik Sipil dan Perencanaan, 2025)
Lighting quality in educational laboratories plays a crucial role in supporting visual comfort, health, and accuracy during practical activities. According to the Indonesian National Standard (SNI 03-7062-2004), the minimum required illuminance for laboratories is 500 lux. This study aims to evaluate the lighting level in the Physics Laboratory at Universitas Negeri Yogyakarta by comparing natural lighting (lamps off) and combined natural–artificial lighting (lamps on). Measurements were conducted using a digital lux meter at a working plane of 0.80 m across 25 grid points. Data collection was carried out at three time intervals—morning (09.00–10.00), noon (12.00–13.00), and afternoon (15.00–16.00)—with three replications each. Results show that natural lighting alone cannot meet the standard, with maximum values of only 217.89 lux at noon and as low as 33.15 lux in the afternoon. In contrast, artificial lighting significantly increased illuminance, reaching 568 lux in the morning, 620.1 lux at noon, and 500.46 lux in the afternoon—all above the required minimum. It is concluded that artificial lighting is essential to maintain adequate and stable illuminance in the laboratory. Regular maintenance and energy-efficient lamp systems are recommended to ensure both compliance and sustainability.